Dialog Budaya Dalam Suku Batak Toba: Dari Agama Sipelebegu Menuju Kepada Paham Kristiani - Marbun, Kembarto (Perspektif, 2018)
This article describes a deep relationship between the traditional culture and modern one in the Batak Toba tribe, North Sumatra. The so-called Sipelebegu Religion, which is a traditional religion in the Batak Toba tribe, has undergone a transformation towards modern Christianity. The Sipelebegu Religion was born of a myth. This myth is the embryo of the birth of Sipelebegu religion, until finally the appreciation of the traditional faith of the Batak Toba community turned to the faith of the modern religion that is Christianity